Breaking the spectral degeneracies in black hole binaries with fast timing data: the hard state of Cygnus X-1. Issue 1 (7th July 2018) - Axelsson, Magnus; Done, Chris
ABSTRACT: The spectra of black hole binaries in the low/hard state are complex, with evidence for multiple different Comptonization regions contributing to the hard X-rays in addition to a cool disc component. We show this explicitly for some of the best RXTE data from Cyg X-1, where the spectrum strongly requires (at least) two different Comptonization components in order to fit the continuum above 3 keV, where the disc does not contribute. However, it is difficult to constrain the physical properties of these Comptonization components uniquely using spectral data alone. Instead, we show that additional information from fast variability can break this degeneracy. Specifically, we use the observed variability power spectra in each energy channel to reconstruct the energy spectra of the variability on time-scales of ∼10, 1, and 0.1 s. The two longer time-scale spectra have similar shapes, but the fastest component is dramatically harder, and has strong curvature indicating that its seed photons are not from the cool disc. We interpret this in the context of propagating fluctuations through a hot flow, where the outer regions are cooler and optically thick, so that they shield the inner region from the disc. The seed photons for the hot inner region are then from the cooler Comptonization region rather than the disc itself.